Enhancing SME Performance through Collaborative Networks,Digitalization Technology, Competence, and Business Resilience: A Study of the Chip Industry in Malang Raya - Isaskar, Riyanti; Puteri, Alya S.; Setiawan, Budi; Riana, Fitria D.; Gutama, Wisynu A.; Andriani, Dwi Retno (Jurnal Dinamika Manajemen, 2025)
This research aims to fill the knowledge gap by understanding that strategic resources such as collaboration networks, technology digitalization, and financial literacy contribute to improving performance through financial and business competencies and resilience in the perspective of a Resource-Based View (RBV). The study was conducted in Malang Raya, which has a dynamic agro-tourism area but is facing market pressure and high competition. It involved 50 chip MSME players who have been operating for at least two years. The research method uses the SEM-PLS on seven main variables: collaboration network, digitalization, financial literacy, competence, financial resilience, business resilience, and business performance. The results show that the three main resources have a significant effect on performance improvement, either directly or through strengthening competence and resilience. This research provides a theoretical contribution by expanding the application of RBV in the context of traditional food MSMEs, as well as presenting an integrative model to improve the competitiveness of MSMEs. Further research is recommended to explore external variables such as regulation and the dynamics of the growing digital market.